Impact of sowing dates and crop geometry on chickpea yield attributes, production and profitability - Sangeeta Choudhary; P.K. Tyagi; K.C. Shukla; Kanchan Khushwa; Ankit Kumar Shridhar; Sonali Singh (Annals of Agricultural Research, 2023)
A field experiment was carried out to study the effect of sowing dates and crop geometry on growth and yield of chickpea during 2020-21 at College of Agriculture Tikamgarh (M.P.). The experiment was laid out in a split plot design with three replications consist treatment of three sowing dates viz., 5 November, 25 November and 15 December and four crop geometries viz., 30×10 cm, 30×15 cm, 45×10 cm and 45×15 cm as main plot and sub plot treatments, respectively. The crop sown on 5 November resulted in higher number of pods plant-1 (106), 100 seed weight (16.84 g) seed yield (2134 kg ha-1), straw yield (3501 kg ha-1), biological yield (5635 kg ha-1), harvest index (37.92%), gross returns (`113714 ha-1), net returns (`69267 ha-1) and B:C ratio (2.56) compared to other sowing dates sown chickpea crop. However, sowing dates were failed to influence the number of seeds pod-1 significantly. Similarly, number of pods plant-1 (78), number of seeds plant-1 and 100-seed weight were found significantly higher with crop geometry 45×15 cm. However, the highest seed yield (1775 kg ha-1), biological yield (4919 kg ha-1), harvest index (35.70%), gross returns ( 95054 ha-1), net returns (`50602 ha-1) and B:C ratio (2.14) were obtained significantly with crop geometry 30 ×10 cm as compared to other crop geometries. The year field study concluded that chickpea crop sown on 5 November exhibited significantly better growth and development over rest of the sowing dates. Among the crop geometry, 45×15 cm was found significantly superior in terms of growth and development over other geometries.